Why Dont We Tax the Rich? Inequality, Legislative Malapportionment, and Personal Income Taxation around the World - Martin Ardanaz; Carlos Scartascini (Inter-American Development Bank (IDB), 2011)
Personal income taxation remains relatively low in many developing countries despite recent democratic advancement and rapid economic growth; this is hard to reconcile with standard political economy models of taxation. This paper argues that the details of political institutions help to explain these low levels of personal income taxation. In particular, legislative malapportionment enables rich elites to have disproportionate political influence. Because over-represented districts tend to be dominated by parties aligned with the elite, these groups can block legislative attempts to introduce progressive taxes. Using a sample of more than 50 countries (including 17 across Latin America) between 1990 and 2007, this paper finds that i) countries with historically more unequal distributions of wealth and income systematically present higher levels of legislative malapportionment, and ii) higher levels of malapportionment are associated with lower shares of personal income taxes in GDP.
Keywords: D70; D78; H24; 330